COVID -19 pandemic : a litmus test of the resilience of Chinese and US governance models - Mao, Dun; Lee, Pei May (Penerbit Universiti Kebangsaan Malaysia, 2022)
The article is an exploratory study to understand the United States and Chinese governments’ response, with different governance models, to the COVID-19 pandemic. This article looks at both governments’ initial reactions during the crisis, how essential resources were managed, and the interplay between government and civil society during the containment phase. This qualitative study uses a case study method to explore the contemporary phenomenon of COVID-19. It draws on secondary data such as government and international organisation reports, newspaper articles, journal articles, and books. The findings reveal that a top-down government structure has provided greater leeway to respond to the crisis, as exemplified by China. Since this research is a preliminary study, the authors do not draw far-reaching conclusions about which model fared better in the management of the pandemic; nevertheless, the analysis notes the increased capacity of governments to act during public health crises if power and resources are concentrated, including the ability to mobilise civil actors to help with the problem. Assessing the response of the U.S. and Chinese governments significantly contributes to the literature on governance and crisis management, and thus benefits both pundits and policymakers.